Impact of Banking Products and MSME Strategies on Poverty Reduction and SDG Achievement: A Pathway to Financial Inclusion - Widhya Sedana Putra P, Komang (WELFARE Jurnal Ilmu Ekonomi, 2025)
This study examines the effect of banking products and MSMEs strategies towards poverty reduction and SDGs achievement. The aim of this paper is to identify what avenues banking products affect financial inclusion and MSMEs strategies resulting in poverty reduction. This study applies a quantitative approach using Partial Least Square-SEM. Data were collected through structured Likert-scale questionnaires from 150 MSMEs in Denpasar, selected purposively based on business legality and their current or potential use of banking products. Based on the partial least square structural equation modeling analysis, the research findings show that while banking products have a significant impact on the financial inclusions and strategies of MSMEs, they play a huge role in poverty reduction. It is not banking products per se that accomplish the poverty reduction directly, but it provides greater access to finance that would otherwise be available to MSMEs to utilize for economic development strategies, and thereby employment creation. The findings of the study reveal that to be able to contribute meaningfully towards SDG, poverty reduction has to be combined with banking products by MSME-focused strategies and financial knowledge. The study promotes inclusive financial systems and special financial services as the driver of economic empowerment and sustainable poverty reduction.Penelitian ini mengeksplorasi bagaimana produk perbankan dan strategi UMKM berkontribusi pada pengurangan kemiskinan dan mendukung pencapaian Tujuan Pembangunan Berkelanjutan (SDGs). Tujuan penelitian ini adalah untuk menyelidiki jalur-jalur melalui produk perbankan yang memengaruhi inklusi keuangan dan strategi UMKM, yang pada akhirnya mendorong pengurangan kemiskinan. Penelitian ini menggunakan pendekatan kuantitatif dengan analisis Partial Least Square-SEM. Data dikumpulkan melalui kuesioner skala Likert dari 150 UMKM di Denpasar yang dipilih secara purposive berdasarkan legalitas usaha dan keterkaitan dengan produk perbankan. Analisis yang dilakukan melalui Partial Least Squares Structural Equation Modeling (PLS-SEM) menunjukkan bahwa produk perbankan memiliki pengaruh signifikan terhadap inklusi keuangan dan strategi UMKM, yang pada gilirannya berdampak signifikan pada pengurangan kemiskinan. Meskipun produk perbankan sendiri tidak secara langsung mengurangi kemiskinan, produk tersebut memfasilitasi akses keuangan yang lebih besar dan memberdayakan UMKM untuk menerapkan strategi pertumbuhan yang mendorong pembangunan ekonomi dan penciptaan lapangan kerja. Temuan ini menunjukkan bahwa upaya pengurangan kemiskinan harus mengintegrasikan produk perbankan dengan strategi berbasis UMKM dan literasi keuangan untuk dapat berkontribusi secara efektif pada pencapaian SDGs. Penelitian ini menekankan pentingnya sistem keuangan inklusif dan layanan keuangan yang terarah dalam mendorong pemberdayaan ekonomi dan pengurangan kemiskinan yang berkelanjutan.